2012
DOI: 10.1136/jnnp-2012-303524.178
|View full text |Cite
|
Sign up to set email alerts
|

Q08 Potential neuroprotective effects of pridopidine in Huntington's disease

Abstract: BackgroundHuntington's disease (HD) is a neurodegenerative disorder characterised by hyperkinetic movements (chorea), cognitive and psychiatric dysfunction. The disease is caused by an expanded polyglutamine stretch in huntingtin (Htt). mHtt interferes with different cellular functions increasing susceptibility of neurons to apoptosis, which ultimately results in neurodegeneration of the striatum and cortex. Recent evidence indicates that dopamine signalling is also impaired in HD, suggesting dopaminergic circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Dopamine stabilizers show some characteristics which are not usually associated with D 2 R ligands, such as pro-cognitive actions in natural forgetting and scopolamine-induced amnesia (Nilsson and Carlsson 2013 ), neuroprotective effects in in vitro and in vivo models of Huntington’s disease (Ruiz et al 2012 ; DiPardo et al 2013 ), and increased social interaction in the MK-801 rat model of social withdrawal in schizophrenia (Rung et al 2005 ). In this context, the substantial occupancy of sigma-1R by pridopidine at 3 and 15 mg/kg, as demonstrated in the present study, is of particular interest since sigma-1R ligands have been shown to possess anti-amnesic and neuroprotective actions, efficacy against negative symptoms in schizophrenia, and positive modulatory effects on NMDA receptor activity (Maurice and Su 2009 ; Hayashi et al 2011 ; van Waarde et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine stabilizers show some characteristics which are not usually associated with D 2 R ligands, such as pro-cognitive actions in natural forgetting and scopolamine-induced amnesia (Nilsson and Carlsson 2013 ), neuroprotective effects in in vitro and in vivo models of Huntington’s disease (Ruiz et al 2012 ; DiPardo et al 2013 ), and increased social interaction in the MK-801 rat model of social withdrawal in schizophrenia (Rung et al 2005 ). In this context, the substantial occupancy of sigma-1R by pridopidine at 3 and 15 mg/kg, as demonstrated in the present study, is of particular interest since sigma-1R ligands have been shown to possess anti-amnesic and neuroprotective actions, efficacy against negative symptoms in schizophrenia, and positive modulatory effects on NMDA receptor activity (Maurice and Su 2009 ; Hayashi et al 2011 ; van Waarde et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the induction of the immediate-early gene Arc (a marker of synaptic activity) by pridopidine in prefrontal cortex, which again is not observed with other D 2 R antagonists or agonists, nondopaminergic effects of pridopidine have been postulated, which would involve an increase in cortical N -methyl-D-aspartate (NMDA) receptor activity (Ponten et al 2010 ; Waters et al 2014 ). Finally, neuroprotective effects of pridopidine and (−)-OSU6162 have recently been described in in vitro and in vivo models of Huntington’s disease (Ruiz et al 2012 ; DiPardo et al 2013 ). Taken together, the present literature findings suggest additional sites of action for pridopidine besides D 2 R, and as detailed below, we have considered the sigma-1 receptor (sigma-1R) as such an additional target.…”
Section: Introductionmentioning
confidence: 99%